GhLBDs Promote Callus Initiation and Act as Selectable Markers to Increase Transformation Efficiency - Wang, Ye; Yuan, Jiachen; Wei, Xi; Chen, Yanli; Chen, Quanjia; Ge, Xiaoyang (Frontiers in Plant Science, 2022)
Detached organs or differentiated tissues could form a mass of pluripotent cells termed as callus on an auxin-rich medium, the underling molecular mechanism of which remains elusive in cotton. LATERAL ORGAN BOUNDARIED DOAIN (LBD) transcription factor is a key regulator of plant cell totipotency/pluripotency, and a number of cotton GhLBDs with high level differential expression during the callus induction process have been identified. Their overexpression in cotton calli fostered promotions in and callus induction without exogenous auxin. Expression analysis and histological observation using paraffin sectioning suggested that the first 72 hours on culture is a key time point for callus initiation, whereby the GhLBDs showed high transcript abundance and enlarged calli that were rapidly developed from procambium and cambium. GhLBDs expression level could be precisely modulated by a gradient concentrations of exogenous auxin, whereas auxin transport inhibitor TIBA could severely inhibit its expression. The LBD-mediated callus formation was also dependent on the expression levels of GhLBDs. Further, a β-estradiol-inducible promoter pER8 was used to drive LBD18 expression, which led to rapid callus proliferation, suggesting pER8/LBD18 could be used as a selectable marker system to replace the existing antibiotic/herbicide resistance selectable markers in plant transformation. Our study provides new insights for callus initiation regulatory mechanism and strategies for improving transformation efficiency in cotton.